Process for preparing high-value chemicals from bamboos
By using composite catalysts such as supported iron oxide and alkaline earth metal oxide during bamboo pyrolysis, the problems of low calorific value and poor thermal stability of bamboo pyrolysis products are solved, and the effect of efficient preparation of high-value methoxyphenol chemicals is achieved.
Patent Information
- Application Number
- CN202411951038.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The prior art has little research on the preparation of high-value-added chemicals through pyrolysis or catalytic pyrolysis using bamboo as raw materials, and the calorific value of bamboo tar is low and the thermal stability is poor, which limits its application.
Bamboo powder is used as raw material, and a catalytic pyrolysis reaction of 450-500°C is carried out by adding a composite catalyst to a nitrogen atmosphere. The composite catalyst contains at least a supported iron oxide and alkaline earth metal oxide. Through synergistic action, the internal chemical bonds of bamboo are broken, recombined and isomerized, thereby increasing the yield of phenolic products and generating high-value methoxyphenol chemicals.
The yield of phenolic products is significantly improved and high-value methoxyphenol chemicals are efficiently generated, such as guaiacol, 2,6-dimethoxyphenol, 4-methyl guaiacol and 4-ethyl guaiacol, providing an industrial production path for high-value chemicals.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomass catalytic pyrolysis and relates to a process for preparing high-value chemicals from bamboo. Background Art
[0002] As the fourth largest energy source after fossil fuels, biomass has become a key research target in scientific research and industry due to its wide range of sources and green and environmentally friendly characteristics. Biomass energy has many excellent characteristics such as zero carbon emissions, clean, renewable and easy to obtain, and is regarded as the most potential and ideal choice to partially replace fossil energy.
[0003] Biomass pyrolysis is a technology that heats dried and shaped biomass under the protection of inert gas to obtain products such as biochar, biomass tar and pyrolysis gas. Compared with biomass gasification and liquefaction processes, the advantages of biomass pyrolysis are simple process, relatively mild conditions and low production cost.
[0004] As the most abundant renewable biomass raw material in nature, lignocellulose is widely found in wood, bamboo, straw, etc. It is mainly composed of cellulose (accounting for 40%-50%), hemicellulose (accounting for 25%-30%) and lignin (accounting for 20%-30%). Lignocellulosic biomass can be used to prepare biochar, synthesis gas, hydrogen, and can also be catalytically converted to prepare chemicals, such as aromatic hydrocarbons, left-handed glucose, left-handed glucose ketone, furfural, phenolic substances, etc. For example, CN118993863A uses supported Zr, Mn, Zn modified metal Cu-based catalysts to hydrogenolyze biomass, and the yield of the target product cyclopentanone is as high as more than 65%. CN110669056A uses metal-modified aminated zeolite molecular sieve as catalyst and crop straw, wood or wood waste as raw materials to prepare 1-hydroxy-3,6-dioxadicyclo[3.2.1]octan-2-one (LAC), and further regulates the Lewis acid sites in the molecular sieve by metal modification, thereby achieving high yield and selective preparation of LAC. CN116174025A uses bagasse as raw material and rare earth metal-modified ZSM-5 zeolite molecular sieve as catalyst, catalytically pyrolyzes at 500°C in a nitrogen atmosphere, and the obtained liquid product has 2,3-dihydrobenzofuran accounting for 45.86%.
[0005] CN115283006A uses HZSM-5 catalyst modified by ammonium molybdate, and uses pine sawdust as raw material. At 550°C and nitrogen atmosphere, the aromatic carbon yield is 19.5%. Patent CN114989842A uses cotton stalks, wheat straw, chestnut shells, and bamboo chips as biomass raw materials, and after being modified by iron nitrate and calcium nitrate, graded pyrolysis catalysis is performed to obtain bio-oil rich in monocyclic aromatic hydrocarbons. The content of monocyclic aromatic hydrocarbons (benzene, toluene, and p-toluene) in the product is 67.51%.
[0006] In the preparation of phenolic substances, CN116355642A uses zeolite molecular sieve combined with seaweed charcoal to graded catalytic pyrolysis of poplar sawdust to prepare light aromatic hydrocarbons and monophenol products. The monophenol content in the liquid bio-oil is 29.3% and the aromatic hydrocarbon content is 43.3%. CN115888849A uses pine wood as a biomass raw material, carbonizes pine sawdust and loads iron and cobalt elements to obtain a modified activated carbon catalyst. In a nitrogen atmosphere, at 600°C, pine sawdust is pyrolyzed under the catalytic action of the modified activated carbon catalyst. The pyrolysis products are all phenolic compounds, the main product is phenol, and the selectivity reaches 84.01%.
[0007] CN111234848A uses biomass as raw material, and loads ammonium sulfate on biomass by impregnation to obtain loaded biomass; the loaded biomass is pyrolyzed under anaerobic conditions, and the obtained pyrolysis gas is condensed to obtain phenol-rich bio-oil to obtain a liquid yield of 43.6-46.3wt%, and the yield of phenolic substances is only 5.1-5.4wt%.
[0008] CN102199435A uses sodium carbonate as a catalyst and fir sawdust, pine sawdust, straw and pine wood as raw materials to react at 450-480° C. to prepare guaiacol, and the yield of the liquid product is 40.2%-45.5%, and the guaiacol content is 40.19%-45.53%.
[0009] CN112409140A discloses a method for depolymerizing lignin to prepare lignin phenolic monomers. Willow wood chips are used as raw materials and placed in ethylene glycol with a Ru / C catalyst, phosphoric acid is added, and the reaction is carried out at 160-200°C to obtain lignin phenolic monomers, wherein the total yield of propyl guaiacol, propyl syringol, propenyl guaiacol and propenyl syringol is 21.8wt%, wherein the selectivity of propyl guaiacol and propyl syringol is 95.1wt%, and the composition and distribution data of other products are not given.
[0010] As a biomass, bamboo has relatively abundant and concentrated resources in many places in my country. Converting it into high-grade clean energy and high-value chemicals is one of the effective ways to solve energy shortages and environmental pollution. Bamboo pyrolysis can produce bamboo tar, bamboo charcoal and combustible gas. Among them, bamboo tar is the main product of bamboo pyrolysis. It has a complex composition, mainly oxygen-containing compounds, including phenols, ketones, aldehydes, acids, alcohols, furans, hydrocarbons and sugar compounds. It is a potential liquid fuel and chemical raw material. However, due to the high water content, high oxygen content and low pH value of bamboo tar, its calorific value is low, its thermal stability is poor, and it is corrosive, which greatly limits the application of bamboo tar. At present, there are relatively few existing studies on the preparation of high value-added chemicals using bamboo as raw material through pyrolysis or catalytic pyrolysis.
[0011] CN116333773A adopts bamboo dust mixed with ferroferric oxide and / or calcium oxide for catalytic pyrolysis, and while obtaining bamboo tar, reduces its acid content, water content and oxygen content and promotes the conversion of organic components in biological organic matter into high value-added components such as ketones, hydrocarbons, phenols, etc. After adding ferroferric oxide and calcium oxide mixed catalyst to bamboo dust as raw material, compared with single pyrolysis, the water content is reduced from 24.68% to 7.17%, the oxygen content is reduced from 38.48% to 30.75%, and the acid compound content is reduced from 6.72% to 0.98%; at the same time, compared with the use of a single catalyst, the content of phenolic compounds is significantly increased after using the mixed catalyst, from the initial 52.06% to 60.12%, but the composition of the phenolic compounds is not given.
[0012] CN104341273A uses bamboo as a raw material, mechanically mixes it with a palladium-based catalyst, and then rapidly pyrolyzes it in a nitrogen atmosphere at 250° C.-380° C. to obtain a liquid yield of 35.3%-39.6%, and a yield of 4-ethylphenol of 1.6%-2.5%; the content of 4-ethylphenol in the organic liquid product (excluding water) is 10.2%-15.2%.
[0013] CN107337587A crushes and screens bamboo to obtain pyrolysis raw materials, and conducts pyrolysis reaction in an atmosphere where ammonia concentration and inert gas coexist. The obtained phenol-rich liquid oil contains phenol, 2-methylphenol, p-methylphenol, 4-ethylphenol, 2-methoxyphenol, 2-methoxy-4-propenylphenol, 2,6-dimethoxyphenol and other phenolic substances with a selectivity of 60%-65%, but the composition distribution of different phenolic products is not given. .
[0014] CN117902958A discloses a method for extracting 2,6-dimethoxyphenol from bamboo using ethylene glycol solvent thermal method. Bamboo scraps, ethylene glycol and water are added to a hydrothermal kettle, and the temperature is controlled at 200-240°C and maintained for 1-2 hours, and then cooled to room temperature to obtain an ethylene glycol extract. After ether extraction and evaporation of the ether solution, the peak area of 2,6-dimethoxyphenol in the remaining liquid is the largest, accounting for 72%-80%. Because the product mass and the composition distribution of other compounds are not given, the actual yield and selectivity of the target product cannot be known.
[0015] At present, research on the high-value utilization of methoxyphenols based on bamboo biomass is still relatively limited. It is of great significance to develop suitable methods to achieve catalytic pyrolysis of bamboo to produce high-value chemicals. Summary of the invention
[0016] As an important part of biomass resources, bamboo has the significant advantages of abundant resources and rapid growth, and has attracted much attention in the exploration of the global renewable energy and materials field. my country has abundant bamboo resources and relatively concentrated distribution. The conversion of bamboo into high-quality clean energy is undoubtedly a potential and effective way to replace some fossil energy. The differences in composition between bamboo and wood are mainly reflected in chemical composition and physical properties. At the chemical composition level, the chemical composition of bamboo is similar to that of wood. The main difference is that cellulose accounts for 40%-50%, lignin accounts for 25%-35%, and hemicellulose accounts for 15%-30% in wood; while bamboo is mainly composed of cellulose and hemicellulose, and its cellulose content is higher than that of wood. In terms of pyrolysis temperature, the pyrolysis temperature range of wood is usually between 150-270℃; while the pyrolysis temperature range of bamboo is wider, ranging from 100-500℃.
[0017] The purpose of the present invention is to propose a process for preparing high-value chemicals from bamboo, using bamboo dust (bamboo powder) biomass as raw material, adding a composite catalyst during the pyrolysis process, and aiming to utilize the synergistic effect of each component in the composite catalyst of a specific composition to gradually break, reorganize, and isomerize the chemical bonds inside the bamboo, and to change the molecular structure in a directional manner, thereby increasing the yield of phenolic products and efficiently generating high-value methoxyphenol chemicals such as guaiacol, 2,6-dimethoxyphenol, 4-methylguaiacol, and 4-ethylguaiacol. The technical solution provided by the present invention can realize the directional catalytic conversion of biomass, realize the efficient and high-value environmentally friendly utilization of biomass on the one hand, and partially replace fossil energy on the other hand.
[0018] To achieve the above object, the technical solution of the present invention is as follows:
[0019] A process for preparing high-value chemicals from bamboo, wherein cellulose and hemicellulose in bamboo are converted into a variety of methoxyphenol products in the presence of a composite catalyst; the composite catalyst at least comprises supported iron oxide and alkaline earth metal oxide.
[0020] With bamboo dust as raw material and nitrogen as carrier gas, a catalytic pyrolysis reaction is carried out at a reaction temperature of 450-500°C and a pressure of 0.1-0.4MPa.
[0021] The mass ratio of the composite catalyst to the bamboo dust is 0.2-1.5:1.
[0022] The various methoxyphenols include guaiacol, 2,6-dimethoxyphenol, 4-methylguaiacol and 4-ethylguaiacol.
[0023] The iron oxide in the supported iron oxide is a mixture of ferric oxide and ferric oxide, with a content of 10-30%; the carrier is a mixed aluminum oxide and silicon oxide, with a content of 10-40%; and the content of alkaline earth metal oxide is 5-40%.
[0024] The composite catalyst also includes nanometer HZSM-5 molecular sieve with a silicon-aluminum ratio of 20-30, and the content is 1-10%.
[0025] The alkaline earth metal oxide in the composite catalyst includes calcium oxide and / or magnesium oxide.
[0026] The molar ratio of silicon oxide to aluminum oxide in the carrier is 1-15:1.
[0027] The method also includes drying and crushing the bamboo residue. The drying temperature is 80-100° C. and the drying time is 10-12 hours.
[0028] The particle size of the bamboo powder is 40-80 meshes.
[0029] The preparation method of the composite catalyst comprises the following steps:
[0030] (1) preparing an aluminum source into an aqueous solution with a mass concentration of 10-30 wt%, adding a silicon source to the aluminum source aqueous solution at 30-60° C., mixing, rapidly stirring for 3-4 hours, adding an iron salt while stirring, stirring for 2-3 hours, heating to 80-100° C., titrating with a 10%-30% sodium carbonate solution to a pH value of 7-8, reacting for 3-4 hours, cooling and filtering, and washing the filter cake with deionized water until the conductivity of the filtrate is no more than 300 S / m;
[0031] (2) mixing the filter cake, silica sol and / or aluminum sol aqueous solution with alkaline earth metal oxide or a mixture of nano-HZSM-5 molecular sieve and alkaline earth metal oxide and beating the mixture to uniformly prepare a catalyst slurry;
[0032] (3) The catalyst slurry is sent to a spray dryer for drying and granulation, and then calcined to obtain a composite catalyst.
[0033] The silicon source is one or more of water glass, silica sol and sodium metasilicate; the aluminum source is one or more of aluminum sulfate, aluminum trichloride, sodium metaaluminate and aluminum sol; the iron salt is one or more of iron sulfate, iron nitrate and ferric chloride.
[0034] The molar ratio of the silicon source to the aluminum source in step (1) is 1-15:1, wherein the silicon source is calculated as SiO2 and the aluminum source is calculated as Al2O3.
[0035] The molar ratio of the iron salt to the silicon source in step (1) is 1-10:1.
[0036] In step (2), the mass ratio of the silica sol and / or aluminum sol aqueous solution to the filter cake is 1:1; the concentration of the silica sol and / or aluminum sol aqueous solution is 5-10%.
[0037] In step (2), the stirring speed of the pulping tank is not less than 300 rpm, and the pulping time is 10-12 hours.
[0038] During the drying and granulation in step (3), the slurry temperature is 100-150°C, and the air inlet temperature of the dryer is controlled not to exceed 300°C to obtain a powder catalyst after drying and forming, the particles of which are spherical, and the particle size of more than 90% of the particles is controlled to be 40-150 microns.
[0039] In step (3), the calcination temperature is controlled at 600-900° C. and the calcination time is 3-4 hours.
[0040] The beneficial effects of the present invention are as follows:
[0041] The present invention uses bamboo dust as a raw material and performs a catalytic pyrolysis process under the action of a composite catalyst. Through the synergistic effect of the components in the composite catalyst of a specific composition, the chemical bonds inside the bamboo are gradually broken, reorganized, and isomerized, and the molecular structure undergoes a directional change, which ultimately increases the yield of phenolic products and efficiently generates high-value methoxyphenol chemicals, providing a novel and economical technical path for the industrial production of high-value methoxyphenol chemicals. In addition, the catalyst also has the advantages of low cost and easy preparation. Specific implementation methods
[0043] Example 1
[0044] Catalyst preparation: weigh 680 g of anhydrous aluminum chloride and dissolve it in 1000 g of water to prepare an aqueous solution, weigh 1500 g of water glass, stir and dissolve, put the water glass material into the aluminum chloride solution at 35°C and mix, stir rapidly for 3 hours, beat into a paste, add 407 g of anhydrous ferric chloride while stirring, then stir for 2 hours, and heat to 90°C, then titrate with 10% sodium carbonate solution to a pH value of 7-8, react for 3 hours, cool and filter, and wash the filter cake with deionized water until the filtrate conductivity is no more than 300S / m;
[0045] The filter cake was mixed with a 6% silica sol aqueous solution in a ratio of 1:1, and then 100 g of nano HZSM-5 molecular sieve with a silicon-aluminum ratio of 20, 200 g of magnesium oxide and 280 g of calcium oxide were added, and the mixture was mixed and slurried evenly. The stirring speed of the slurrying tank was not less than 300 rpm, and the slurrying time was 11 hours to prepare a catalyst slurry;
[0046] The catalyst slurry was transferred to a spray slurry tank, and the spray dryer was turned on for drying and granulation. The mixing temperature was 100°C, and the inlet temperature of the dryer was controlled at 280°C to obtain a powder catalyst after drying and forming. The particles were spherical, and more than 90% of the particles had a particle size of 40-150 microns. Then it was transferred to a high-temperature converter and calcined at 900°C for 3 hours to obtain 1400 grams of the finished catalyst.
[0047] Bamboo catalytic pyrolysis process: take 400 grams of the finished catalyst, take 500 grams of bamboo powder that has been dried and dehydrated at 95°C for 12 hours and crushed and sieved to 40-80 mesh, mix them in a ratio of 0.8:1 and place them in a mixer for thorough mixing. The mixed materials are loaded into a pyrolysis reactor, and the temperature is raised to 450°C by electric heating and hot nitrogen purging for 15 minutes for pyrolysis reaction. The pressure is maintained at 0.1MPa; the liquid product cooled after the reaction is collected for detection.
[0048] Example 2
[0049] Catalyst preparation: weigh 680 g of anhydrous aluminum chloride and dissolve it in 1000 g of water, weigh 1200 g of silica sol, stir and dissolve, put water glass into the aluminum chloride solution at 35°C, stir rapidly for 3 hours, beat into a paste, add 500 g of ferric sulfate while stirring, then stir for 2 hours, and heat to 90°C, then titrate with 10% sodium carbonate solution to a pH value of 7-8, react for 3 hours, cool and filter, and wash the filter cake with deionized water until the filtrate conductivity is no more than 300S / m;
[0050] The filter cake was mixed with a 6% aluminum sol aqueous solution in a ratio of 1:1, and then 100 g of nano HZSM-5 molecular sieve with a silicon-aluminum ratio of 30, 200 g of magnesium oxide and 280 g of calcium oxide were added, and the mixture was mixed and slurried evenly to prepare a catalyst slurry, wherein the stirring speed of the slurrying tank was not less than 300 rpm, and the slurrying time was 11 hours;
[0051] The catalyst slurry was transferred to a spray slurry tank, and the spray dryer was turned on for drying and granulation. The mixing temperature was 120°C, and the dryer inlet temperature was controlled at 285°C to obtain a powder catalyst after drying and forming. The particles were spherical, and more than 90% of the particles had a particle size of 40-150 microns. Then it was transferred to a high-temperature converter at 900°C and calcined for 3 hours to obtain 1450 grams of the finished catalyst.
[0052] Bamboo catalytic pyrolysis process: take 750 grams of the finished catalyst, take 500 grams of bamboo powder that has been dried and dehydrated at 95°C for 12 hours and crushed and sieved to 40-80 mesh, mix them in a ratio of 1.5:1 and place them in a mixer for thorough mixing. The mixed materials are loaded into a pyrolysis reactor, and the temperature is raised to 450°C by electric heating and hot nitrogen purging for 15 minutes for pyrolysis reaction. The pressure is maintained at 0.2MPa; the liquid product cooled after the reaction is collected for detection.
[0053] Example 3
[0054] Catalyst preparation: Weigh 400 g of sodium aluminate and dissolve it in 1000 g of water, weigh 1000 g of water glass, stir and dissolve, add water glass material into sodium aluminate solution at 35°C, stir rapidly for 3 hours, beat into gel, add 407 g of anhydrous ferric chloride while stirring, then stir for 2 hours, and heat to 90°C, then titrate with 10% sodium carbonate solution to pH 7-8, react for 3 hours, cool and filter, wash the filter cake with deionized water until the filtrate conductivity is not more than 300S / m;
[0055] The filter cake was mixed with an aqueous solution of 3% silica sol and 3% aluminum sol in a ratio of 1:1, and then 100 grams of nano HZSM-5 molecular sieve with a silicon-aluminum ratio of 25, 200 grams of magnesium oxide and 280 grams of calcium oxide were added, and the mixture was mixed and slurried evenly to prepare a catalyst slurry, wherein the stirring speed of the slurrying tank was not less than 300 rpm, and the slurrying time was 11 hours;
[0056] The catalyst slurry was transferred to a spray slurry tank, and the spray dryer was turned on for drying and granulation. The mixing temperature was 125°C, and the dryer inlet temperature was controlled at 290°C to obtain a powder catalyst after drying and forming. The particles were spherical, and more than 90% of the particles had a particle size of 40-150 microns. Then it was transferred to a high-temperature converter at 900°C and calcined for 3 hours to obtain 1400 grams of the finished catalyst.
[0057] Bamboo catalytic pyrolysis process: take 400 grams of the finished catalyst, take 500 grams of bamboo powder that has been dried and dehydrated at 95°C for 12 hours and crushed and sieved to 40-80 mesh, mix them in a mixer at a ratio of 0.8:1 and mix them thoroughly. The mixed materials are loaded into a pyrolysis reactor, and the temperature is raised to 500°C by electric heating and hot nitrogen purging for 15 minutes for pyrolysis reaction. The pressure is maintained at 0.3MPa; the liquid product cooled after the reaction is collected for detection.
[0058] Example 4
[0059] Catalyst preparation: weigh 800 g of aluminum sulfate and dissolve it in 1000 g of water, weigh 1200 g of silica sol, stir and dissolve, put water glass into the aluminum sulfate solution at 35°C, stir rapidly for 3 hours, beat into a paste, add 600 g of ferric nitrate while stirring, then stir for 2 hours, and heat to 90°C, then titrate with 10% sodium carbonate solution to a pH value of 7-8, react for 3 hours, cool and filter, and wash the filter cake with deionized water until the filtrate conductivity is no more than 300S / m;
[0060] The filter cake was mixed with an aqueous solution of 2% silica sol and 6% aluminum sol in a ratio of 1:1, and then 100 grams of nano HZSM-5 molecular sieve with a silicon-aluminum ratio of 25, 200 grams of magnesium oxide and 280 grams of calcium oxide were added, and the mixture was mixed and slurried evenly to prepare a catalyst slurry, wherein the stirring speed of the slurrying tank was not less than 300 rpm, and the slurrying time was 11 hours;
[0061] The catalyst slurry was transferred to a spray slurry tank, and the spray dryer was turned on for drying and granulation. The mixing temperature was 150°C, and the dryer inlet temperature was controlled at 295°C to obtain a powder catalyst after drying and forming. The particles were spherical, and more than 90% of the particles had a particle size of 40-150 microns. Then it was transferred to a high-temperature converter at 900°C and calcined for 3 hours to obtain 1500 grams of the finished catalyst.
[0062] Bamboo catalytic pyrolysis process: take 750 grams of the finished catalyst, take 500 grams of bamboo powder that has been dried and dehydrated at 95°C for 12 hours and crushed and sieved to 40-80 mesh, mix them in a 1.5:1 ratio in a mixer and mix them thoroughly. The mixed materials are loaded into a pyrolysis reactor, heated to 500°C by electric heating and hot nitrogen purging for 15 minutes to carry out pyrolysis reaction, and the pressure is maintained at 0.4MPa; the liquid product cooled after the reaction is collected for detection.
[0063] Example 5
[0064] Catalyst preparation: weigh 680 g of anhydrous aluminum chloride and dissolve it in 1000 g of water, weigh 1200 g of silica sol, stir and dissolve, put water glass into the aluminum chloride solution at 35°C, stir rapidly for 3 hours, beat into a paste, add 500 g of ferric sulfate while stirring, then stir for 2 hours, and heat to 90°C, then titrate with 10% sodium carbonate solution to a pH value of 7-8, react for 3 hours, cool and filter, and wash the filter cake with deionized water until the filtrate conductivity is no more than 300S / m;
[0065] The filter cake was mixed with an aqueous solution of 2% silica sol and 4% aluminum sol in a ratio of 1:1, and then 200 g of magnesium oxide and 280 g of calcium oxide were added, and the mixture was mixed and slurried evenly to prepare a catalyst slurry, wherein the stirring speed of the slurrying tank was not less than 300 rpm, and the slurrying time was 11 hours;
[0066] The catalyst slurry was transferred to a spray slurry tank, and the spray dryer was turned on for drying and granulation. The mixing temperature was 150°C, and the inlet temperature of the dryer was controlled at 295°C to obtain a powder catalyst after drying and forming. The particles were spherical, and more than 90% of the particles were controlled to have a particle size of 40-150 microns. Then it was transferred to a high-temperature converter at 900°C and calcined for 3 hours to obtain 1,300 grams of the finished catalyst.
[0067] Catalytic pyrolysis of bamboo: take 400 g of the finished catalyst, take 500 g of bamboo powder that has been dried and dehydrated at 95°C for 12 h and crushed and sieved to 40-80 mesh, mix them in a ratio of 0.8:1 and place them in a mixer for thorough mixing. The mixed materials are loaded into a pyrolysis reactor, and the temperature is raised to 500°C by electric heating and hot nitrogen purging for 15 minutes for pyrolysis reaction, and the pressure is maintained at 0.4 MPa; the liquid product cooled after the reaction is collected for detection.
[0068] Comparative Example 1
[0069] Bamboo pyrolysis process: Take 1000 grams of bamboo powder that has been dried and dehydrated at 95℃ for 12 hours and crushed and sieved to 40-80 mesh, put it into the pyrolysis reactor, heat it to 500℃ through electric heating and hot nitrogen purging, and keep it at a constant temperature for 15 minutes for pyrolysis reaction. The pressure is maintained at 0.4MPa; collect the liquid sample cooled down after the reaction for detection.
[0070] Comparative Example 2
[0071] Catalyst preparation: weigh 680 g of anhydrous aluminum chloride and dissolve it in 1000 g of water, weigh 1200 g of silica sol, stir and dissolve, put water glass into the aluminum chloride solution at 35°C and mix, stir rapidly for 3 hours, beat into a paste, add 407 g of anhydrous ferric chloride while stirring, then stir for 2 hours, and heat to 90°C, then titrate with 10% sodium carbonate solution to a pH value of 7-8, react for 3 hours, cool and filter, and wash the filter cake with deionized water until the filtrate conductivity is no more than 300S / m;
[0072] The filter cake was mixed with a 6% silica sol aqueous solution in a ratio of 1:1 and beaten evenly to prepare a catalyst slurry, wherein the stirring speed of the beating tank was not less than 300 rpm and the beating time was 11 hours;
[0073] The catalyst slurry was transferred to a spray slurry tank, and the spray dryer was turned on for drying and granulation. The mixing temperature was 150°C, and the dryer inlet temperature was controlled at 285°C to obtain a powder catalyst after drying and forming. The particles were spherical, and more than 90% of the particles had a particle size of 40-150 microns. Then it was transferred to a high-temperature converter at 900°C and calcined for 3 hours to obtain about 1,370 grams of the finished catalyst.
[0074] Bamboo catalytic pyrolysis process: Take 400 grams of catalyst, pre-dry and remove water at 95℃ for 12 hours, and crush 500 grams of bamboo powder into 40-80 mesh, place it in a mixer and mix it thoroughly. The mixed materials are loaded into a pyrolysis reactor, and the temperature is raised to 500℃ by electric heating and hot nitrogen purging for 15 minutes for pyrolysis reaction. The pressure is maintained at 0.4MPa; the liquid product cooled after the reaction is collected for detection.
[0075] Table 1 shows the analysis results of the liquid phase pyrolysis oil products obtained from the bamboo residues of the above control examples and examples under different conditions and catalysts. Table 2 shows the selectivity of different phenolic products in the examples and comparative examples: methoxyphenols (guaiacol, 2,6-dimethoxyphenol, 4-methylguaiacol, 4-ethylguaiacol), phenol, m-cresol, p-cresol and 4-ethylphenol.
[0076] The results show that: Comparative Example 1 is a pyrolysis process of bamboo under catalyst-free conditions, and the main products are phenols and ketone products, wherein the yield of phenols is 39.64%, the yield of ketone products is 36.26%, the yield of alcohol products is 6.76%, and the others are 7.71%. From the perspective of the composition of phenolic products, its products are mainly phenol and 4-ethylphenol, and there are very few high-value methoxyphenol products. Comparative Example 2 is a catalytic pyrolysis of bamboo using a supported iron-based catalyst, and the yield of phenolic substances is significantly increased to 56.34% compared with Comparative Example 1, ketone products are reduced (24.84%), and alcohol products are increased. It is shown that the catalytic active center of supported iron oxide is conducive to decomposing cellulose and hemicellulose into phenolic products. However, from the perspective of the composition of phenolic products, its products are still mainly phenol and 4-ethylphenol, and the selectivity of methoxyphenol is only 5.43%. It is shown that the catalytic pyrolysis process of supported iron oxide catalyst can change the breaking and recombination mode of chemical bonds in bamboo, and improve the yield of phenolic products.
[0077] Embodiment 5, adopt this technical scheme, with the composite catalyst of supported iron oxide, calcium oxide and magnesium oxide, the process of catalytic pyrolysis of bamboo, compared with comparative examples 1, 2, greatly improves the yield of phenolic substances to 64.21%, the yield of ketone products is reduced to 9.21%, but the yields of alcohols and other products are still relatively high, 7.19% and 10.74% respectively. From the perspective of the composition of phenolic products, the yields of products such as phenol, methylphenol and ethylphenol are greatly reduced, and the selectivity of methoxyphenol products is greatly improved to 35.12%. It is explained that the synergistic effect of calcium oxide and magnesium oxide in the composite catalyst causes the oxygen-containing compounds in bamboo tar to reorganize, improves the yield of phenolic products, and is conducive to the generation of high-value methoxyphenol products.
[0078] In Examples 1-4, the present technical solution is adopted to catalyze the pyrolysis of bamboo using a catalyst composed of supported iron oxide, nano-HZSM-5 molecular sieve, calcium oxide and magnesium oxide. The yield of phenolic substances is further increased to more than 69% compared with Example 5, and the yield of alcohols and other products is greatly reduced to less than 1%. Among the phenolic products, the selectivity of methoxyphenol products is further improved. This shows that the synergistic effect of the nano-HZSM-5 molecular sieve in the composite catalyst causes the oxygen-containing compounds in the bamboo tar to reorganize and isomerize, and the molecular structure undergoes a directional change, and a high-value methoxyphenol product is efficiently generated.
[0079] The process of preparing high-value chemicals from bamboo proposed by the present invention can not only increase the content of phenolic substances, but also improve the selectivity of high-value products such as methoxyphenol, phenol, m-cresol, p-cresol and 4-ethylphenol, thus creating good conditions for subsequent utilization.
[0080] The above is only an excellent embodiment of the present invention and cannot limit the present invention. Any modification, equivalent replacement, improvement and other behaviors within the spirit and principle of the present invention shall fall within the protection scope of the present invention.
[0081] Table 1 Analysis results of liquid phase pyrolysis oil products obtained from bamboo residue under different conditions and catalysts in comparative examples and examples
[0082]
[0083] Table 2 Selectivity of phenolic substances in Examples and Comparative Examples
[0084]
Claims
1. A process for producing high-value chemicals from bamboo, characterized in that: Cellulose and hemicellulose in bamboo are converted into a variety of methoxyphenol products in the presence of a composite catalyst; the composite catalyst at least contains supported iron oxide and alkaline earth metal oxide.
2. A process for producing high-value chemicals from bamboo according to claim 1, characterized in that: Bamboo dust is used as a raw material, and a catalytic pyrolysis reaction is carried out in a nitrogen atmosphere at 400-500°C and 0.1-0.4MPa; the mass ratio of the composite catalyst to the bamboo dust is 0.2-1.5:1; the multiple methoxyphenols include guaiacol, 2,6-dimethoxyphenol, 4-methylguaiacol and 4-ethylguaiacol.
3. A process for producing high-value chemicals from bamboo according to claim 1, characterized in that: The iron oxide in the loaded iron oxide is a mixture of ferric oxide and ferroferric oxide, with a content of 10-30%; the carrier is a mixed aluminum oxide and silicon oxide, with a content of 10-40%; and the content of alkaline earth metal oxide is 5-40%.
4. A process for producing high-value chemicals from bamboo according to claim 1 or 3, characterized in that: The composite catalyst also includes nanometer HZSM-5 molecular sieve with a silicon-aluminum ratio of 20-30, and the content is 1-10%.
5. A process for producing high-value chemicals from bamboo according to claim 1 or 3, characterized in that: The alkaline earth metal oxide in the composite catalyst includes calcium oxide and / or magnesium oxide; and / or the molar ratio of silicon oxide to aluminum oxide in the carrier is 1-15:
1.
6. A process for producing high-value chemicals from bamboo according to claim 1, characterized in that: The bamboo powder is dried and crushed to a size of 40-80 meshes.
7. A process for producing high-value chemicals from bamboo according to claim 1, characterized in that: The preparation process of the composite catalyst specifically comprises the following steps: (1) preparing an aluminum source into an aqueous solution with a mass concentration of 10-30 wt%, adding a silicon source to the aluminum source aqueous solution at 30-60° C., mixing, rapidly stirring for 3-4 hours, adding an iron salt while stirring, stirring for 2-3 hours, heating to 80-100° C., titrating with a 10%-30% sodium carbonate solution to a pH value of 7-8, reacting for 3-4 hours, cooling and filtering, and washing the filter cake with deionized water until the conductivity of the filtrate is no more than 300 S / m; (2) mixing the filter cake, the silica sol and / or aluminum sol aqueous solution with the alkaline earth metal oxide or the mixture of nano-HZSM-5 molecular sieve and alkaline earth metal oxide and beating them uniformly to prepare a catalyst slurry; (3) The catalyst slurry is sent to a spray dryer for drying, granulation and high-temperature calcination to obtain a composite catalyst.
8. A process for producing high-value chemicals from bamboo according to claim 1, characterized in that: In step (1), the silicon source is one or more of water glass, silica sol and sodium metasilicate; the aluminum source is one or more of aluminum sulfate, aluminum trichloride, sodium metaaluminate and aluminum sol; the iron salt is one or more of iron sulfate, iron nitrate and iron trichloride; and / or, The molar ratio of the iron salt to the silicon source is 1-10:
1.
9. A process for producing high-value chemicals from bamboo according to claim 1, characterized in that: In step (2), the mass ratio of the silica sol and / or aluminum sol aqueous solution to the filter cake is 1:1; the concentration of the silica sol and / or aluminum sol aqueous solution is 5-10%.
10. A process for producing high-value chemicals from bamboo according to claim 1, characterized in that: During the drying and granulation in step (3), the slurry temperature is 100-150°C, the air inlet temperature of the dryer is controlled not to exceed 300°C; the particle size of the pellets is controlled to be 40-150 microns; the roasting temperature is controlled to be 600-900°C, and the roasting time is 3-4 hours.
Citation Information
Patent Citations
Method for preparing 4-ethylphenol by performing catalytic pyrolysis on biomass
CN104341273A
Method for preparation of phenol-rich liquid oil by utilizing biomass
CN107337587A
Method for preparing LAC by catalyzing cellulose / biomass pyrolysis with metal modified ammoniated molecular sieve
CN110669056A
Method for co-production of phenol-rich bio-oil and super capacitor material by biomass pyrolysis
CN111234848A
Method for preparing lignin phenolic monomers by depolymerizing lignin
CN112409140A